The Smart Narrative of a Smart City - Gonella, Francesco (Frontiers in Sustainable Cities, 2019)
Current narrative about Smart Cities is basically flawed at two levels. First, it describes cities whose promise of smartness is highly biased. Second, it neglects the systemic nature of the urban metabolism, as well as the role of the support region of the city in terms of resource provision. In this contribution, I propose a short review of the mainstream Smart City narrative elements as presented by influential and authoritative sources, pointing out their detachment from the reality and from the sustainability of cities described by systemic thinking.